2019
DOI: 10.3390/su11216153
|View full text |Cite
|
Sign up to set email alerts
|

A Text Analytics-Based Importance Performance Analysis and Its Application to Airline Service

Abstract: We introduce a new importance-performance analysis (IPA) methodology while making use of direct service experience perceptions represented by online reviews with numerical ratings. The proposed IPA, which we call the text analytics-based IPA (TAIPA), allows the real-time calculation of importance using the probability distribution of word frequency via the latent Dirichlet allocation (LDA) application to online reviews, and of performance using numerical rating values. The importance is also adjusted with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 89 publications
0
10
0
Order By: Relevance
“…Compared with manual topic modeling, automatic topic modeling not only has the advantage of being faster when processing larger data sets, but it also incorporates less human intervention, resulting in more objective results. Latent Dirichlet allocation (LDA), a state-of-art topic modeling tool, is both capable and suitable to automatically perform the topic identification task [27][28][29] such that a qualitative review is thereby quantifiable by calculating the weight of topics within [30,31].…”
Section: Ugc Analysis Techniquesmentioning
confidence: 99%
“…Compared with manual topic modeling, automatic topic modeling not only has the advantage of being faster when processing larger data sets, but it also incorporates less human intervention, resulting in more objective results. Latent Dirichlet allocation (LDA), a state-of-art topic modeling tool, is both capable and suitable to automatically perform the topic identification task [27][28][29] such that a qualitative review is thereby quantifiable by calculating the weight of topics within [30,31].…”
Section: Ugc Analysis Techniquesmentioning
confidence: 99%
“…Further, we will mention relatively recent studies where IPA was applied in its standard or improved form. For example, revised forms of IPA are applied in air transport by Lin and Vlachos (2018), Hongli (2018), andNam andLee (2019). Standard IPA has been successfully applied to public bus transportation by Chaisomboon et al (2020) and Esmailpour et al (2020).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…It should be emphasized that the IPA technique is seeking to widen its topics of interest. This research can be seen in different optimizations proposed both to overcome several important drawbacks of the IPA matrix in its standard form (Mount, 2000;Oh, 2001;Bacon, 2003;Ban et al, 2016Ban et al, , 2019 and to assess the impact of new business requests such as digitization or moving towards green products/processes (Patiar et al, 2017;McLeay et al, 2017;Nam & Lee, 2019;Chaisomboon et al, 2020;Esmailpour et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The usefulness of the memory needs to be optimized; it can be found that long text and short text have a high degree of overlap in terms. Therefore, based on the characteristics of short text and traditional feature filtering methods, the long text features and short text common features are left, and the superior information is added to the short text classification process (Nam and Lee, 2019 ). An improved conditional random field model is also proposed, which treats the tendency analysis of phrase sentiment as sequence labeling (Hahn et al, 2020 ).…”
Section: Dynamic Evolution Mechanism Of Digital Entrepreneurship Ecosystem Based On Text Sentiment Calculation Analysismentioning
confidence: 99%